The poetry of nature - Bandari; Prime Music ([S.l : Jingo Records, 2008)
The Music of Nature has been proven to have a therapeutic effect on the human body. It stabilizes human emotions, rids fatigue, relaxes human cells, and strengthens metabolism without side effects. This 3CD set contains the 3 latest albums by the renowned Bandari Orchestra from Switzerland. Inspired by nature and composed of the purest, most ancient elements, every track in this collection resonates with a gentle absolute quality - to soothe the mind and body, anytime and anywhere
Vol.1 The alps - Vol.2 Vienna forest - Vol.3 Rhine river
Title from container
Artist: BANDARI
Keywords: Music therapy; Music for relaxation; Nature sounds